Unesco's current and projected social science programmes. (International Social Science Journal, 1973)
The article presents the United Nations Educational, Scientific, and Cultural Organization's (UNESCO) current and projected social science programs. The 17th General Conference of UNESCO approved a two-year budget from UNESCO's regular program resources and from United Nations Development Programme (UNDP) funds for the program in social sciences. In the draft outline plan for the six-year period 1973-78 two points about social sciences were generally accepted. One was that it is important that UNESCO provide effective leadership to the international community of social scientists and concern itself with methodology, organization of research and international exchange at the advanced level. The second point is the paramount necessity to arrange through UNESCO and in other ways for social scientists from developing countries to take part as full participants at the cutting edge of contemporary research. To promote exchanges between social scientists from countries with different social and economic systems, seminars on research and teaching in international relations, international law and international organization will be organized to emphasize the impact of science and technology on international relations, including space explorations, the world-wide transfer of technology and the uses of the oceans.